Management of Necrotizing Fasciitis and Fecal Peritonitis following Ostomy Necrosis and Detachment by Using NPT and Flexi-Seal - Fahri Yetışır; Akgün Ebru Şarer; H. Zafer Acar (Case Reports in Surgery)
Management of necrotizing fasciitis and severe faecal peritonitis following ostomy in elderly patient with comorbid disease is challenging. We would like to report management of frozen Open Abdomen (OA) with colonic fistula following ostomy necrosis and detachment in an elderly patient with comorbid disease and malignancy. 78-year-old woman with high stage rectum carcinoma was admitted to emergency department and underwent operation for severe peritonitis and sigmoid colonic perforation. Loop sigmoidostomy was performed. At postoperative 15th day, she was transferred to our clinic with necrotizing fasciitis and severe faecal peritonitis due to ostomy necrosis and detachment. Enteric effluent was removed from the OA wound by using the Flexi-Seal Fecal Management System (FMS) (ConvaTec) and pesser tube in deeply located colonic fistula in conjunction with Negative Pressure Therapy (NPT). Maturation of ostomy was facilitated by using second NPT on ostomy side. After source control, delayed abdominal closure was achieved by skin flap approximation.